STUDY ON INFLUENCE OF RESIN CONTENT OVER MAIN PROPERTIES OF DRY-FORMED HARDBOARDS - Savov, Viktor (Innovation in Woodworking Industry and Engineering design, 2012)
Fiberboards are homogeneous wood-based composite material with dispersion phase – wood fibers and matrix of adhesion and cohesion binders formed between the elements. The importance of this two binder types for board‟s properties depends from manufacturing processes. The adhesion binders have main significance at dry-processes manufacturing.At the report is presented study on influence of resin content over main properties of dry formed hardboards, produced from hardwood on the base of phenol-formaldehyde resin. For the purpose is implemented experiment in laboratory conditions. The correlation coefficient and functional subjections of fiberboard's properties from resin content are determinate. It is conducted analyze of the results and proper conclusions are made.